Field Test Study on the Interactions Between "Cold Wet Island Effect" and Frosting-Defrosting Phenomenon for Air Source Heat Pump Array - LIANG Shimin; WANG Zhe; GAO Xuefeng; YAN Yueru; WANG Gang; HU Songtao; WANG Hongwei (Zhileng xuebao)
With the expansion of air source heat pump (ASHP) heating systems, ASHP arrays have become the main arrangement for medium to large-scale heating projects. However, the "cold island effect" and "wet island effect" are prone to form at the center of ASHP arrays, leading to frequent frosting and defrosting in the heat pump units. Conversely, frequent frosting and defrosting also affect the "cold-wet island effect" in ASHP array. To explore the mutual influences between the "cold and wet island effect" and the phenomena of frosting and defrosting, this study was based on an ASHP array heating demonstration project in Weihai, Shandong Province, and established an field testing platform and carried out field measurements. Typical day testing results indicated that, under the influence of the "cold-wet island effect," the defrosting frequency of units at the center of the array increased by 225 % compared to those on the periphery. Frequent defrosting reduced the cold island effect intensity of the central units by 4.3 %, and increased the wet island effect intensity by 3.9 %, although the effect was not significant. Additionally, the nominal heating capacity loss coefficient during the frosting-defrosting cycle for the central units increased by 59.3 %, and their average heating capacity and COP decreased by 31.6 % and 34.0 %, compared to the peripheral units, indicating significant performance degradation in the central units. This study revealed and quantified the mutual influence between the "cold and wet island effect" and the frosting and defrosting processes in ASHP units, which provided theoretical support for the large-scale application and efficient operation of ASHPs.